Determinant factors of Total Quality Management (TQM) and Human Capital Management (HCM) for product quality improvement in herbal industry in Malaysia - Mazita, Mokhtar; Wan Khairul Anuar, Wan Abdul Manan; Ida Rizyani, Tahir; Azizan, Azit; Siti Maryam Shaidatul, Khamdi (Researchfora International Conference, Hong Kong, 2018)
This study was to determine which factors of Total Quality Management (TQM) and Human Capital Management (HCM) that improve product quality of herbal industry in Malaysia. To establish a flexible data collection tool, a questionnaire was developed to measure the outcomes of herbal product quality. Regression analysis and confirmatory factor analysis were utilized to test the hypotheses claim in the study. It was found that quality maintenance and visionary leadership were having a high beta coefficient with product quality, confirming that maintenance of quality is a more important factor that increases product quality and customer satisfaction in the contexts of Malaysian herbal industry. Consequently, this study provided further evidence of the hypothesis made. Through these findings, the quality standard of Malaysian herbal products will be achieved and established.